Real-time averaging of position data from multiple GPS receivers. (August 2016) - Schrader, Daniel K.; Min, Byung-Cheol; Matson, Eric T.; Eric Dietz, J.
Highlights: A simple, inexpensive method to improve consumer-grade GPS is described. System is "hot-swappable" with any GPS receiver that outputs NMEA 0183 protocol. Output is real-time; no post-processing is required. GPS data fusion is done solely by low-power, 8-bit microcontrollers. System show superior accuracy and reliability over a single GPS receiver. Abstract: Making GPS more accurate and/or reliable by combining it with other sensors and applying sophisticated data processing techniques has been attempted many times. Our approach to enhancing the performance of GPS is much simpler than most. We combine multiple (up to eight) consumer-grade GPS receivers into a system that averages their data in real time, requiring no other sensors, augmentation technologies, or powerful processors. The results show significant improvement in both accuracy and reliability of the data over that of a single receiver, and the distribution of error more closely resembles the normal distribution (as compared to a single receiver). Our multi-GPS system shows potential to be an inexpensive way to achieve better GPS performance with only "off-the-shelf" equipment.